MAO-A Inhibitor Properties by Molecular Modeling Method, Antimicrobial Activity and Characterization of Silver Nanoparticles Synthesized from Lactifluus Bertillonii Mushroom - Keşkek Karabulut, Yasemin; Yiğit, Aybek; Tunç, Ayşe Karacalı; Sarıtaş, Büşra Merve; Kesici, Sedat; Uzun, Yusuf; Sadullahoglu, Cemil (My University, 2024)
This work focuses on the antimicrobial activity of AgNPs produced using a green, environmentally friendly synthesis process from Lactifluus bertillonii mushrooms using the minimum inhibitory concentration (MIC) method. Additionally, the inhibitory characteristics of the chemicals present in the mushroom extract are also determined. SEM, TEM, UV-vis, and FT-IR instruments are employed as part of the study. The average particle size in the characterisation was determined by the imaging program to be 10.471 nm. Additionally, the activity of AgNPs against Klebsiella pneumoniae was found to be 512 µg/ml in the antimicrobial activity tests carried out using the MIC method, which yields more sensitive results. The target enzyme for treating depression, the MAO-A enzyme, whose 2Z5X coding structure was derived from humans, was employed in docking research. The three dimensional structures of Isoquercitrin (-8.2 kcal/mol), Rutin (-9.3 kcal/mol), Fisetin (-8.2 kcal/mol), Chrysin (-9.4 kcal/mol), Quercetin (-10.6 kcal/mol), Naringenin (8.8 kcal/mol), Kaemferol (-10.8 kcal/mol) and Luteolin (-10.8 kcal/mol) were optimized in the Gaussian09 program using the DFT/B3LYP/6-31G(d,p) basis set. Then, binding energies of these structures were determined with the help of the AutoDock Vina software. Their binding energies have been shown to indicate that they possess the property of MAO-A inhibitors.
Keywords: Green synthesis; Docking; AgNPs; Lactifluus bertillonii; MAO-A enzyme